1972
DOI: 10.1159/000130179
|View full text |Cite
|
Sign up to set email alerts
|

Absence of correlation between XX/XY chimerism in the liver and the first signs of freemartinism in the calf fetus

Abstract: XX/XY chimerism has been studied in the liver of 22 presumptive freemartin fetuses and in 12 male cotwins of multiple pregnancies, at an age of 39 to 62 days post-insemination. At these stages, the majority of the liver cells are hematopoietic cells. In these fetuses, the degree of chimerism varies from 0% to 55 %. Except for one case, the cells of the host predominate, i.e., the percentage of XY cells in freemartins is less than 50 % and is of the same order of magnitude as the number of XX cells in the male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous reports have shown the relative proportion of XY to XX in karyotypes of freemartins was not related with the degree of masculinization ( Peretti et al, 2008 ; Kozubska-Sobocinska et al, 2011 ; Szczerbal et al, 2014 ). It has also been reported that the proportion of XY cells had no relation to the inhibition degree of ovary or of Müllerian duct ( Vigier, Prepin & Jost, 1972 ). However, no report has shown the relationships between fertility and degree of masculinization in heterosexual twin female, thus the relationship between XY cells and fertility of heterosexual twin female remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown the relative proportion of XY to XX in karyotypes of freemartins was not related with the degree of masculinization ( Peretti et al, 2008 ; Kozubska-Sobocinska et al, 2011 ; Szczerbal et al, 2014 ). It has also been reported that the proportion of XY cells had no relation to the inhibition degree of ovary or of Müllerian duct ( Vigier, Prepin & Jost, 1972 ). However, no report has shown the relationships between fertility and degree of masculinization in heterosexual twin female, thus the relationship between XY cells and fertility of heterosexual twin female remains unknown.…”
Section: Discussionmentioning
confidence: 99%